2006
DOI: 10.1001/archsurg.141.8.790
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Bleeding Complications After Pharmacologic Deep Venous Thrombosis Prophylaxis

Abstract: Hypothesis: Major bleeding complications from pharmacologic deep venous thrombosis (DVT) prophylaxis are infrequent. Design: Systematic review of the MEDLINE database from 1965 to August 2005, using the terms DVT, prophylaxis, general surgery, and heparin. Setting and Patients: Randomized controlled trials evaluating pharmacologic DVT prophylaxis in patients undergoing general surgery. Main Outcome Measures: Eight complication categories: injection site bruising, wound hematoma, drain site bleeding, hematuria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 32 publications
3
84
1
Order By: Relevance
“…Another meta-analysis reported that the mean risk of wound hematoma and bleeding requir ing reoperation in the control groups of randomized trials of thromboprophyaxis with LDUH or LMWH were 0.8% and 0.7%, respectively. 95 When making trade-offs between benefi ts and harms of pharmacologic prophylaxis, we estimated that the baseline risk of major bleeding is 1.8 times greater in high-risk patients based on data from Cohen et al 96 VTE. A systematic review of 37 studies of varying design concluded that obesity is a risk factor for VTE in both medical and bariatric surgical patients.…”
Section: Baseline Risk Risk Factors and Risk Stratifi Cation For Mamentioning
confidence: 99%
“…Another meta-analysis reported that the mean risk of wound hematoma and bleeding requir ing reoperation in the control groups of randomized trials of thromboprophyaxis with LDUH or LMWH were 0.8% and 0.7%, respectively. 95 When making trade-offs between benefi ts and harms of pharmacologic prophylaxis, we estimated that the baseline risk of major bleeding is 1.8 times greater in high-risk patients based on data from Cohen et al 96 VTE. A systematic review of 37 studies of varying design concluded that obesity is a risk factor for VTE in both medical and bariatric surgical patients.…”
Section: Baseline Risk Risk Factors and Risk Stratifi Cation For Mamentioning
confidence: 99%
“…Meta-analyses have shown that , 1% of patients require an additional operative procedure because of chemoprophylaxis-associated bleeding. 31 However, the available meta-analysis data examined the surgical population as a whole. Bleeding risk was not stratifi ed by VTE risk, which is a marker of the aggressiveness of prophylaxis regimen.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…5 The benefits of VTE chemoprophylaxis are high but should be considered in light of the risk of VTE and of bleeding complications, for which data are conflicting. 6,7 Studies estimating the incidence of VTE in diverse populations of otolaryngology patients reported rates between 0.1% and 0.3% for DVT and 0.05% and 0.2% for PE, which are much lower than in other surgical populations. 8,9 The reported incidence was 6 times higher among patients undergoing head and neck procedures compared with those undergoing general otolaryngology procedures (0.6% vs 0.1%) because of higher risks associated with older age and malignancy.…”
mentioning
confidence: 99%